2021
DOI: 10.1002/prot.26157
|View full text |Cite
|
Sign up to set email alerts
|

The functional motions and related key residues behind the uncoating of coxsackievirus A16

Abstract: The coxsackievirus A16 (CVA16) is a highly contagious virus that causes the hand, foot, and mouth disease, which seriously threatens the health of children. At present, there are still no available antiviral drugs or effective treatments against the infection of CVA16, and thus it is of great significance to develop anti‐CVA16 vaccines. However, the intrinsic uncoating property of the capsid may destroy the neutralizing epitopes and influence its immunogenicity, which hinders the vaccine developments. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This motion results in the collapse of the regions around the fivefold axes and expansion outward of the regions around the twofold and quasi threefold axes. A similar rotation motion has also been observed in the intrinsic motions of other virus capsids, for example, enterovirus 71­(EV71) and coxsackievirus A16­(CVA16) . The third motion mode that mostly contributes to the opening of the twofold channels is shown in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This motion results in the collapse of the regions around the fivefold axes and expansion outward of the regions around the twofold and quasi threefold axes. A similar rotation motion has also been observed in the intrinsic motions of other virus capsids, for example, enterovirus 71­(EV71) and coxsackievirus A16­(CVA16) . The third motion mode that mostly contributes to the opening of the twofold channels is shown in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Fox et al also shows that some mutations that stabilize the PV capsid in the unexpansive conformation existed in the canyon region . The study of He et al also revealed that several sites in the canyon region significantly regulated the uncoating of coxsackievirus A16 capsid . Reisdorph et al found that the mobility of the canyon region is critical for the capsid uncoating of rhinovirus, which is structurally similar to PV, and the binding of antiviral drugs or residue mutations in this region can block the functional motions of the virus …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations